Global research landscape on learning innovation in physical education: trends, collaboration networks, and future directions (2013–2022) - Suwarni; Perdima, Feby Elra; Lobo, Joseph (UIR Press Bekerjasama dengan International Association of Physical Education and Sports, 2025)
Background: Innovation in physical education (PE) plays a key role in enhancing students’ cognitive, affective, and psychomotor development. However, there is limited comprehensive mapping that captures global research trends, influential contributors, and thematic evolution related to learning innovation in PE over the past decade. Objectives: The objective of this study is to analyse publication trends, leading sources, influential authors and affiliations, collaboration networks, and thematic keyword patterns in global research on learning innovation in physical education from 2013–2022. Methods: A bibliometric analysis was conducted using Scopus-indexed journal articles (n = 867). Data were processed through VOSviewer (v1.6.19) and Publish or Perish to examine publication growth, prolific authors, affiliations, countries, journals, and keyword co-occurrence networks. Finding/Results: Publications showed a steady increase, peaking in 2022 (179 documents). Physical Education and Sport Pedagogy emerged as the most productive journal, while Universidad de Oviedo and China were the leading institutional and national contributors. Keyword clustering revealed five dominant themes: models-based practice, learning motivation, health-oriented PE, teacher professional development, and curriculum design. Conclusion: This study maps the global landscape of learning innovation in PE and highlights the growing shift toward learner-centred, theory-driven, and technology-enhanced pedagogical models. Future research should expand cross-regional collaboration, integrate multi-database analyses, and explore thematic evolution to capture dynamic shifts in PE innovation.